2004
DOI: 10.1177/153537020422900206
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Inflammation is a Complex Response Based on the Pathological Expression of the Nervous, Immune, and Endocrine Functional Systems

Abstract: The successive phases that make up both the local and systemic posttraumatic acute inflammatory response could represent the expression of three concatenated pathological or "primitive" functional systems with trophic properties: the nervous, immune, and endocrine ones. The nervous functional system would play an important role in the phenomenon of ischemia-reperfusion, which would be represented by nutrition by diffusion that is either anaerobic (ischemia) or with defective use of oxygen (reperfusion) and, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
155
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(159 citation statements)
references
References 110 publications
0
155
0
4
Order By: Relevance
“…It was suggested that systemic treatment with p53-activating chemotherapeutics might enhance antitumor responses of normal macrophages without augmenting pro-tumor functions of tumor associated macrophages (TAMS). The hypoxic nature of the TME determines the types of inflammatory cells that infiltrate, typically favoring those that depend on the glycolytic pathway for survival [125,126]. Certain phenotypes of the TAMS and neutrophils are largely associated with promoting tumor cell growth, and NF-κB signaling plays a key role in controlling these phenotypes [127].…”
Section: Targeting Constituents Within the Tumor Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that systemic treatment with p53-activating chemotherapeutics might enhance antitumor responses of normal macrophages without augmenting pro-tumor functions of tumor associated macrophages (TAMS). The hypoxic nature of the TME determines the types of inflammatory cells that infiltrate, typically favoring those that depend on the glycolytic pathway for survival [125,126]. Certain phenotypes of the TAMS and neutrophils are largely associated with promoting tumor cell growth, and NF-κB signaling plays a key role in controlling these phenotypes [127].…”
Section: Targeting Constituents Within the Tumor Microenvironmentmentioning
confidence: 99%
“…4. Various nanoformulations for co-delivery of therapeutics with normalized pharmacokinetics and pharmacodynamics, including self-assembled nanoscale coordination polymer [158], cholesterol-based chimeric nanoparticle [157], thermosensitive hydrogel [123], mesoporous silica nanoparticle [125], and liposomes [124].…”
Section: Combined Gene and Chemotherapymentioning
confidence: 99%
“…This type of metabolism is characterized by a large production of adenosine triphosphate (ATP), which is used to drive specialized multiple cellular processes. 7,9,10 Because the nervous, immune, and endocrine phases of the inflammatory response progress from ischemia to the development of an oxidative metabolism, it also is tempting to speculate on whether the body reproduces the successive stages by which life passes from its origin without oxygen until it develops an effective, although costly, system for the use of oxygen every time we suffer posttraumatic acute inflammation. 9,10 Likewise, the successive expression of these three functional systems during embryonic development and also during the evolutionary development of our species may explain why the inflammatory response is a ubiquitous mechanism that is common to multiple diseases, because it is an integrator of the ontogeny and phylogeny.…”
Section: The Possible Trophic Significance Of the Inflammatory Responmentioning
confidence: 99%
“…9,10 Likewise, the successive expression of these three functional systems during embryonic development and also during the evolutionary development of our species may explain why the inflammatory response is a ubiquitous mechanism that is common to multiple diseases, because it is an integrator of the ontogeny and phylogeny. 7 …”
Section: The Possible Trophic Significance Of the Inflammatory Responmentioning
confidence: 99%
See 1 more Smart Citation